The dynamic analysis of kreiss conveyers with using computer - Fuesun, Ahsverisci; Huseyin, Bayiroglu (AMER INST PHYSICS, 2007)
The changes of the quantity of motion parameters have been represented by graphics using mathematica programme. Obtained results are compared the results in the literature and it is realized that the general tendency are approximately same.
Keywords: Kreiss conveyers; crank-and-rod mechanism; Physics